Selective Inhibition of Janus Kinase 3 Has No Impact on Infarct Size or Neurobehavioral Outcomes in Permanent Ischemic Stroke in Mice - DeMars, Kelly M.; Pacheco, Sean C.; Yang, Changjun; Siwarski, David M.; Candelario-Jalil, Eduardo (Frontiers in Neurology, 2017)
Janus kinase 3 (JAK3) is associated with the common gamma chain of several interleukin receptors essential to inflammatory signaling. To study the potential role of JAK3 in stroke-induced neuroinflammation, we subjected mice to permanent middle cerebral artery occlusion, and investigated the effects of JAK3 inhibition with decernotinib (VX-509) on infarct size, behavior, and levels of several inflammatory mediators. Results from our double immunofluorescence staining showed JAK3 expression on neurons, endothelial cells, and microglia/macrophages in the ischemic mouse brain (n=3). We found for the first time that total as well as phosphorylated/activated JAK3 are dramatically increased after stroke in the ipsilateral hemisphere (**P<0.01; n=5-13/group) in addition to increased IL-21 expression after stroke (**P<0.01; n=5-7/group). However, inhibition of JAK3 confirmed by reduced phosphorylation of its activation loop at tyrosine residues 980/981 does not reduce infarct volume measured at 48 h after stroke (n=6-10/group) nor does it alter behavioral outcomes sensitive to neurological deficits or stroke-induced neuroinflammatory response (n=9-10/group). These results do not support a detrimental role for JAK3 in acute neuroinflammation following permanent focal cerebral ischemia. The functional role of increased JAK3 activation after stroke remains to be further investigated.